Implementation of Bubble Sort to Sort Positive Integers in Ascending Using the Flowgorithm Application - Jabar, Ami Abdul; Indrayani, Maida; Parhusip, Nelviony; Nasution, Darmeli (Bahasa Indonesia, 2024)
This research utilizes computer technology and software as effective learning media. The Bubble Sort algorithm was chosen because it is simple but effective in sorting data. Using Flowgorithm as a visualization tool makes it easier to understand the algorithm and ensures correct implementation. The research methodology includes literature study, analysis of data sorting characteristics, and application of algorithms in Flowgorithm. The results show that Bubble Sort succeeded in sorting the data correctly according to ascending order, confirming the usefulness of the Flowgorithm application in learning algorithms and programming.